To Enhance Web Search Based on Topic Sensitive_Social Relationship Ranking Algorithm in Social Networks - Park, GunWoo; Lee, SooJin; Lee, SangHoon (Proceedings of the 2009 IEEE/WIC/ACM International Joint Conference on Web Intelligence and Intelligent Agent Technology - Volume 03, 2009)
Social Network Services(SNS) such as Facebook, Friendster, MySpace and Orkut have established themselves as very popular and powerful tools for making and finding friends and for identifying other people who share similar interests. Search behavior of Web users often reflects that of others who have similar interests or similar information profiles in social networks. Therefore, if we locate web users interested in certain topics or areas and then keep track of their preferences in terms of Web search results, we can pinpoint relevant and reliable information about these people in a timely manner In this paper, we present an efficient search system called SMART Finder. This system supports efficient search results for locating people whose social relationships are highly ranked according to specific topics. It can also identify people who are highly associated with each other with regard to Web search topics. Our results are supported by experiments on Orkut and Facebook.